Characterization of laboratory coagulation parameters and risk factors for intraventricular hemorrhage in extremely premature neonates. (22nd May 2022) - Roberts, Jonathan C.; Javed, M. Jawad; Lundy, Molly K.; Burns, Rita M.; Wang, Huaping; Tarantino, Michael D.
Abstract: Background: Extremely premature neonates have increased risk for bleeding, perhaps the most devastating version of which being intraventricular hemorrhage (IVH). Limited data are available for coagulation parameters in this vulnerable population. Objectives: We conducted a prospective cohort study characterizing coagulation laboratory parameters in extremely premature neonates 23–30 weeks gestational age (GA) and determined coagulation parameters and clinical risk factors associated with IVH. Patients/Methods: One hundred twenty neonates 23–30 weeks GA were enrolled, and umbilical cord blood samples were obtained and processed at the time of birth. Coagulation parameters including prothrombin time (PT), international normalized ratio (INR), activated partial thromboplastin time (APTT), and activity assays for factors II, VII, IX, X, XIII, and XIII subunit A antigen were performed by standard methods. Clinical risk factors were analyzed for association with IVH. Results: Of the enrolled neonates, 29 (24.2%) experienced IVH. Persistent pulmonary hypertension (PPHN) independently predicted IVH risk with odds ratio (OR) 5.3 (95% confidence interval [CI] 1.1–24.3), P = .0338; and chronic lung disease (CLD) approached significance with OR 2.3 (95% CI 0.9–5.5), P = .0659. Coagulation parameters were evaluated for association with IVH, and there was no significant difference among coagulation tests in neonates with or without IVH or per GA. Reduced factor XIII subunit A showed significant association with death, P = .003. Conclusions: We present a large, prospective study of laboratory coagulation parameters in extremely premature neonates, including factor X, factor XIII, and factor XIII subunit A not previously described in this population. These findings may impact clinical practice and should encourage additional study in this vulnerable population.